Different strokes: winning strategies in women's (and men's) big bash cricket - Massey, P.; Hogan, V. (Journal of Sports Economics, 2025)
Women's professional sport has generally been underrated due to stereotypical perceptions that women are less skilled than men. If, as some experimental studies suggest, women perform less well under pressure than men, this may result in women adopting more cautious or defensive styles of play which fans find less attractive. We analyse winning strategies in the Australian Men's and Women's Big Bash Cricket Leagues (MBBL and WBBL) in order to assess whether the WBBL is characterised by more cautious/defensive playing strategies than the MBBL. The two leagues are (almost) identical in all aspects other than gender and thus provide an ideal environment to test for differences in playing strategies. Our results do not suggest that teams` playing strategies are more defensive in the WBBL than the MBBL. If anything, they indicate that attacking play is more likely to win in the WBBL.